Perancangan Media Pembelajaran Bilingual dan Analisisnya - Rosyidah, Ummi; Stevano, Marshelino; Rachmawati S, Aulia Intan; Kholifah, Laela Musri; Faris, Muhammad Rafli Al; Widagdo, Arif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Bilingual education plays an important role in improving students' language competence and cultural understanding, the success of which depends on interactive, contextual, and developmentally appropriate learning media. This research aims to design bilingual-based learning media that is in accordance with the characteristics of students and the curriculum, as well as to analyze its effectiveness and implementation in the learning process.This research uses a qualitative approach with the type of literature review. Data collection is done by literature review through identification, collection, and selection of literature. The results obtained in this study are that in the context of bilingual learning, the media not only functions to provide material understanding for students but also as a means to increase students' vocabulary and skills in foreign languages, especially English. Therefore, the right learning media is needed to convey the material so that the learning objectives are achieved optimally.